1970
DOI: 10.1111/j.1365-2621.1970.tb00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Ph ADJUSTMENT CONTROL OF OXIDATIVE OFF‐FLAVORS DURING GRINDING OF RAW LEGUME SEEDS

Abstract: SUMMARY— Grinding dry California Small White beans or Lee soybeans under acid conditions inhibited lipoxidase in the seeds and resulted in bland legume slurries and “milks.” Sensory evaluation and gas chromatography were used to determine the effect of processing method on flavor. Off‐flavor development was suppressed at pH 3.85 and below; acidification to about pH 2.0 was necessary to obtain maximum protein extraction in the preparation of legume “milk.” Acceptable bland products were obtained from the slurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

1973
1973
1999
1999

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 12 publications
0
17
0
3
Order By: Relevance
“…Numerosas tentativas têm sido feitas com a finalidade de melhorar o sabor (Hand et al, 1964;Wilkens et al, 1967;Badenhop & Hackler, 1970;Khaleque et al, 1970;Kon et al, 1970;Nelson et al, 1976;Omosaiye & Cheryan, 1979). Dentre estas, destacam-se: (a) moagem do grão com água quente a 1 Aceito para publicação em 2 de julho de 1998.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Numerosas tentativas têm sido feitas com a finalidade de melhorar o sabor (Hand et al, 1964;Wilkens et al, 1967;Badenhop & Hackler, 1970;Khaleque et al, 1970;Kon et al, 1970;Nelson et al, 1976;Omosaiye & Cheryan, 1979). Dentre estas, destacam-se: (a) moagem do grão com água quente a 1 Aceito para publicação em 2 de julho de 1998.…”
Section: Introductionunclassified
“…4 Economista Doméstica, aluna de Pós-graduação da UFV, CEP 36570-000 Viçosa, MG. 5 Economista Doméstica, aluna de Pós-graduação da UFRRJ. 80-100ºC (Wilkens et al, 1967); (b) branqueamento (Nelson et al, 1976); (c) moagem do grão em baixo pH seguido de cozimento (Kon et al, 1970); e (d) maceração do grão em meio alcalino (Badenhop & Hackler, 1970). Os produtos obtidos por estes processos tem melhor sabor, porém, pode ocorrer, em alguns casos, a perda de solubilidade das proteínas, diminuindo a sua extratibilidade.…”
Section: Introductionunclassified
“…Numerosas tentativas têm sido feitas para a melhoria de sabor dos produtos de soja (Badenhop & Hackler, 1970;Khaleque et al, 1970;Kon et al, 1970;Nelson et al, 1976); dentre estas, o processo usado por Nelson et al (1976), na elaboração de leite de soja, tem sido considerado bastante viável, e foi baseado no branqueamento do grão de soja, seguido de desintegração e homogeneização à alta pressão, obtendo-se o leite de soja com sabor suave.…”
Section: Introductionunclassified
“…They showed that lipoxygenase causes off-flavor, and rapid hydration and high temperature grinding prevents offflavor development. Several studies have confirmed this concept (Mustakas et al, 1969;Kon et al, 1970;Wolf, 197 5;Sessa and Rackis, 1977). Absence of the off-flavors in the properly blanched products emphasizes that the formation is due to enzymatic reaction rather than autoxidation of the oil CSnyder, 1973;Kalbrener et al, 1974;Sessa and Rackis, 1977).…”
Section: Flavors Of Soymilkmentioning
confidence: 57%
“…The protein is ground into a fine state, formulated by addition of ingredients to make the milk similar to cow's milk and homogenized. Kon et al (1970) used low pH to prevent the oxidative off-flavor formation during grinding of raw legume seeds.…”
Section: Soymilk Preparationmentioning
confidence: 99%